Synovial inflammation does not change in the absence of effective treatment: implications for the use of synovial histopathology as biomarker in early phase clinical trials in rheumatoid arthritis. Issue 8 (13th January 2006) - Baeten, D; Houbiers, J; Kruithof, E; Vandooren, B; Van den Bosch, F; Boots, A M; Veys, E M; Miltenburg, A M M; De Keyser, F
Abstract : Objectives: To determine the impact on synovial histopathology of changes in clinical disease activity in the absence of effective treatment. Methods: Twelve patients with active RA not receiving effective treatment were studied over a 14 week period. Synovial biopsy specimens obtained at baseline and week 14 were analysed by histology and immunohistochemistry. Results: Over the course of 14 weeks, there was a trend towards a decrease of the DAS28, with 7/12 patients being good or moderate DAS28 responders despite the absence of effective treatment. Patients' assessment of global disease activity and swollen joint count both decreased significantly. Histologically, there was a decrease of lining layer hyperplasia and lymphoid aggregates, a similar trend for vascularity, but there was no effect on global synovial infiltration. Accordingly, there was no decrease of the cellular infiltration with T lymphocytes (CD3, CD4, CD8), B lymphocytes (CD20), plasma cells (CD38), dendritic cells (CD1a, CD83), and even an increase of CD163+ sublining macrophages, with a similar trend for CD68+ sublining macrophages. The changes in DAS28 scores in these patients did not correlate with changes in histological variables, with the exception of an inverse correlation with plasma cells. Remarkably, even in the DAS28 responders, no significant changes in synovial inflammatory infiltration were noted. Conclusions: Despite variations in global disease activity, synovial inflammatory infiltration did not change significantly in the absence of effective treatment. The lack of a placebo effect on synovial markers of treatment response such as sublining macrophages can facilitate conclusive early phase trials with small numbers of patients with RA.